Python programming in context - Miller, Bradley N.; Ranum, David L.; Anderson, Julie, 1947- (Burlington, Massachusetts : Jones & Bartlett Learning, 2021)
"Python Programming in Context, Third Edition is designed for the undergraduate programming course using the Python language. It can also be utilized at the high school level. Despite being an older title, Python Programming in Context is still extremely popular, especially as the usage and interest in Python as a programming language continues to grow. At SIGCSE 2018, it was the third most requested title. Currently 81 schools use the second edition of this title"--
Introduction to Python -- Python: estimating Pi -- Codes and other secrets -- Introducing the Python collections -- File input and output -- Image processing -- Data mining: cluster analysis -- Cryptanalysis -- Fractals: the geometry of nature -- Astronomy -- Bears, fish, and plants, oh my! -- Your father was a rectangle -- Video games.
Includes bibliographical references and index.
Keywords: Python (Computer program language)